Optimising inoculum yield and shelf life of Plectosphaerella cucumerina, a potential bioherbicide for Cirsium arvense. Issue 12 (2nd December 2017) - Bailey, K. L.; Derby, J.; Bourdôt, G. W.; Skipp, R. A.; Hurrell, G. A.
ABSTRACT: Plectosphaerella cucumerina was identified as a potential bioherbicide for controlling Cirsium arvense in Canada and New Zealand. The current study evaluated production conditions using two isolates (one from each country) to determine whether the yield and shelf life of inoculum are suitable for mass production. Mycelial growth and sporulation in culture both increased from 15°C to 25°C and declined at higher temperatures with no mycelial growth at 37°C. The Canadian isolate produced fewer conidia than a New Zealand isolate. Potato dextrose-based liquid media with moderate to high concentrations of carbohydrates (25%, 50%, and 100%) maximised conidia production and these base media produced conidia with the highest germination rate (>80%) both at harvest and after 4 weeks stored at 4°C in 2.5% glycerol, 40% milk glycerol or after air drying. However, after 10-week storage, the conidia failed to germinate. Sporulation occurred during growth on all solid substrates tested (rice, rolled barley, and triticale), but conidial germination was highest on rice and barley, both before and after air drying. By contrast to conidia, 90% of mycelia-infested barley grains were viable after 3 years of storage at room temperature, although viability was lost by this time on the other substrates. This study has shown that the nutritional base is an important determinant of sporulation and shelf life for P. cucumerina . Although the yield of conidia in liquid medium was adequate to justify further development of P. cucumerina as a bioherbicide, improvement in its shelf life, or alternate formulation types that extend the shelf life, must be made for commercial efficiency.